O regime de resolução bancária no ordenamento de São Tomé e Príncipe - Pires, Nayda Indhira Silveira D'Almeida (2022)
The legal regime for the prevention, restructuring, resolution and liquidation of banking institutions in force in São Tomé and Príncipe aims to safeguard the financial soundness of banks in crisis, the interests and confidence of depositors and the stability of the financial system, by following, roughly, the international guidelines and practices, with some specificities arising from the national context, in particular as regards the implementation of resolution measures, the financing of restructuring and resolution measures and the liquidation regime, raising some relevant practical issues. These issues, which are analyzed in this dissertation, show the inadequacy of the restructuring and resolution regime as conceived and applied in other systems, due to the small size of the São Tomé and Príncipe’s financial system, giving rise to the recommendation for introduction of conjunctural adjustments regarding the implementation of restructuring and resolution measures, the financing of such measures and the liquidation of banks in crisis.